Abortion provision in Northern Ireland: the views of health professionals working in obstetrics and gynaecology units. Issue 1 (4th March 2021) - Bloomer, Fiona; Kavanagh, Jayne; Morgan, Leanne; McLaughlin, Laura; Roberts, Ralph; Savage, Wendy; Francome, Colin
Abstract : Introduction: Abortion became decriminalised in Northern Ireland in October 2019. Until that point there existed no evidence concerning the views of health professionals on decriminalisation or on their willingness to be involved in abortion care. The purpose of this study was to address this lack of evidence, including all categories of health professionals working in obstetrics and gynaecology units in Northern Ireland. Methods: The online survey was targeted at medical, nursing and midwifery staff working in the obstetrics and gynaecology units in each Health and Social Care (HSC) Trust in Northern Ireland. The survey was issued via clinical directors in each Trust using the REDCap platform. Results: The findings showed widespread support for decriminalisation of abortion up until 24 weeks' gestation (n=169, 54%). The majority of clinicians stated they were willing to provide abortions in certain circumstances (which were undefined) (n=188, 60% medical abortions; n=157, 50% surgical abortions). Despite regional variation, the results show that there are sufficient numbers of clinicians to provide a service within each HSC Trust. The results indicate that many clinicians who report a religious affiliation are also supportive of decriminalisation (n=46, 51% Catholic; n=53, 45% Protestant) and are willing to provide care, countering the assumption that those of faith would all raise conscientious objections to service provision. Conclusions: The findings of this study are very encouraging for the development, implementation and delivery of local abortion care within HSC Trusts in Northern Ireland and should be of value in informing commissioners and providers about the design of a service model and its underpinning training programmes.